Legal Analysis of Real Estate Transfer Taxation Provisions in Notarial Transaction Agreements in the Context of the Digitalization of Society 5.0 - Siahaan, Albert (International Publisher (YAPENBI), 2023)
This study aims to find alternative ways to use digital technology to solve the problem of applying land and building taxes in deeds of sale and purchase. Real estate transfer tax is mandatory in notarized transaction contracts and is levied according to the law. The real estate transfer tax is composed of income tax, value added tax, sales tax on luxury goods and the fee for transferring the title deed. The tax is calculated according to the Regional Tax and Equalization Law and is based on the maximum value of the sale or transaction value of the taxable property. This leads to legal uncertainty, as there are many cases where the basis of calculation has been invented to reduce the tax due before the contract is signed. This leads to a great potential loss for the State if the calculation is based on the Regional Tax and Equalization Law. This study is a normative legal research using books, laws, articles and other legal materials. The results indicate that the basis for calculating property transfer tax in notarial transaction agreements should not be taken from the highest value between the Sales Value of the Taxable Object or transaction value, but rather from the fair market value. The Regional Tax and Retribution Law should be revised with the support of digitalization so that tax potential can increase.